Computed Tomography, Coronary Angiography, and Intravascular Ultrasound in the Diagnosis of Left Anterior Descending Stenosis in a 38-Year-Old Woman with a Calcium Score of Zero - Malgorzata Zalewska-Adamiec; Slawomir Dobrzycki (Diagnostics)
Cardiovascular diseases, including coronary artery disease, are the leading cause of mortality in the general population. The likelihood of significant coronary artery disease occurring in young women (<40 years of age) is very low. Diagnosis is challenging and often delayed, treatment tends to be suboptimal, and the long-term prognosis is poor. We present the case of a 38-year-old woman with typical anginal chest pain whose coronary computed tomography angiography (CCTA) revealed significant narrowing in the left anterior descending artery (LAD) despite a coronary artery calcium score (CACS) of zero. To assess the significance of the lesion, coronary angiography and intravascular ultrasound (IVUS) were performed, which revealed borderline narrowing. Conservative treatment was recommended.